Landscape and Ecological Engineering - Natuhara, Yosihiro; Lee, Dong Kun.; Yoshimura, Chihiro; Chang, Chun-Yen.; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer.)
Landscape and Ecological Engineering is published by the International Consortium of Landscape and Ecological Engineering (ICLEE) in the interests of protecting and improving the environment in the face of biodiversity loss, desertification, global warming, and other environmental conditions. The journal invites original papers, reports, reviews and technical notes on all aspects of conservation, restoration, and management of ecosystems. It is not limited to purely scientific approaches, but welcomes technological and design approaches that provide useful and practical solutions to today's environmental problems. The journal's coverage is relevant to universities and research institutes, while its emphasis on the practical application of research will be important to all decision makers dealing with landscape planning and management problems.
Keywords: Regional planning; Urban planning; Landscape ecology; Plant ecology; Civil engineering; Environmental management; Nature conservation; Landscape Ecology; Nature Conservation; Civil Engineering; Environmental Management; Landscape/Regional and Urban Planning; Plant Ecology